miR-7 Modulates hESC Differentiation into Insulin-Producing Beta-like Cells and Contributes to Cell Maturation - Javier López-Beas; Vivian Capilla-González; Yolanda Aguilera; Nuria Mellado; Christian C. Lachaud; Franz Martín; Tarik Smani; Bernat Soria; Abdelkrim Hmadcha (Elsevier, 2018)
Human pluripotent stem cells retain the extraordinary capacity to differentiate into pancreatic beta cells. For this particular lineage, more effort is still required to stress the importance of developing an efficient, reproducible, easy, and cost-effective differentiation protocol to obtain more mature, homogeneous, and functional insulin-secreting cells. In addition, microRNAs (miRNAs) have emerged as a class of small non-coding RNAs that regulate many cellular processes, including pancreatic differentiation. Some miRNAs are known to be preferentially expressed in islets. Of note, miR-375 and miR-7 are two of the most abundant pancreatic miRNAs, and they are necessary for proper pancreatic islet development. Here we provide new insight into specific miRNAs involved in pancreatic differentiation. We found that miR-7 is differentially expressed during the differentiation of human embryonic stem cells (hESCs) into a beta cell-like phenotype and that its modulation plays an important role in generating mature pancreatic beta cells. This strategy may be exploited to optimize the potential for in vitro differentiation of hESCs into insulin-producing beta-like cells for use in preclinical studies and future clinical applications as well as the prospective uses of miRNAs to improve this process. Keywords: hESCs, HS181, differentiation, beta cell, microRNA, miR7, insulin, endoderm, maturation, pluripotent, Pdx-1, Gene Ontology, KEGG